New Directions in Religious Experience - Nordby, Kevin (My University, 2020)
Chapter One An Argument Concerning the Epistemic Status of Religious Experience I endeavor to show that the skeptic, even on her own terms, will never succeed in ruling out all beliefs based on religious experience by claiming they are unjustified. There is a sort of religious belief based on religious experience that, to my knowledge, skeptical thinkers have not yet considered. The expression of this sort of religious belief bears certain resemblances to natural expressions and avowals of self-knowledge as understood in Dorit Bar-On’s neo-expressivist account of self-knowledge. I argue that some expressions of religious beliefs formed from religious perceptions are similar enough to self-expressions of inner states (i.e., self-knowledge) to require similar epistemic treatment. First-person ascriptions of internal states to play a very significant and relatively uncontroversial epistemic role. If we are to discount religious experience when expressed this way, we must find an appropriate reason. But, on my account, there is no such reason. Therefore, we must endorse the epistemic significance of religious experience in avowals or pay the costly price of abandoning the role avowals play in our mainstream accounts of self-knowledge. Chapter Two Religious Experience and Commonsense Epistemology It is uncontroversial that William Alston’s doxastic practices approach to epistemology is a suitable home for religious experience. Alvin Plantinga’s reformed epistemology is also compatible with religious experience. What has not been shown, however, is whether any other epistemic frameworks (particularly those not antecedently interested in religious epistemology) are compatible with religious experience. At least one is promising in this regard: commonsense epistemology. In this paper I argue that advocates for the epistemic significance of religious experience will find commonsense epistemology just as hospitable a framework for their concerns as Alston’s doxastic practices or Plantinga’s reformed epistemology. I consider six major principles of commonsense epistemology and argue they establish a suitable approach for those who wish to take the epistemic weight of religious experience seriously. The upshot for advocates of religious experience is that commonsense epistemology offers a simpler route (in comparison to Alston or Plantinga) for securing the epistemic status of beliefs based on religious experience. I argue that commonsense epistemology offers the advantage of inheriting minimal theoretical baggage in contrast to the aforementioned religious epistemologies, and it does this while also avoiding the appearance of giving religious subject matter any sort of epistemological special treatment. Chapter Three Putting God in a Box (or a Book) Many theists accept Aquinas’s categories of special and general revelation yet are reluctant to allow religious experience a place in either category. I argue that genuine religious experience, when it obtains, should be considered divine revelation. I present this argument within the framework familiar to those for whom I intend my argument to apply: an evangelical or conservative protestant (henceforth, CP&E) framework. Against many theists who are skeptical of religious experience, the aforementioned way of thinking about divine revelation must be expanded to include religious experience if we are to preserve a traditional understanding of revelation, according to which divine revelation is generally understood as acts of divine agency disclosing something to a human being(s). Further, I argue that holding the New Testament Gospels as revelation entails regarding some religious experiences as divine revelation too, as the Gospels are generally accepted by CP&E to be a historical record of religious events (including religious experiences). Despite the claims of some critics of religious experience, this position does not obligate Christians to believe that religious experiences are infallible; surely, they can go wrong. I show that while we must regard genuine religious experience as constituting divine revelation if we antecedently accept the Gospels as divine revelation, we can do so while still acknowledging the fallibility of religious experience. Ruling out revelation through religious experience also rules out Yahweh speaking to Moses through the burning bush, Saul on the Damascus road, and a great deal more. Devotion to the text may be admirable, but the authority of the text cannot outgrow the authority of its source. Divine revelation (very often unexpected divine revelation) through religious experience is the bedrock of the text. While the inclination may be understandable, surely CP&E cannot disavow the latter to protect the former. Like it or not, we are very poorly placed to judge when divinity is done speaking.
Keywords: Philosophy; Philosophy of Religion; Religious Experience; Religious Epistemology